Seloko Adat Melayu Jambi: Educational Values and Their Relevance in History Learning in High School - Setyanugraha, Aldo Toto; Usman, Saidina; Wahyuni, Anny (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Seloko Adat Melayu Jambi is a form of customary expression rich in life philosophy, moral values, and social guidance; however, its significance has begun to fade as younger generations increasingly struggle to understand the figurative language used in seloko. This condition has resulted in the educational values embedded within it no longer being fully internalized, including within the context of formal education. In history education, seloko holds great potential as a source of learning based on local wisdom that can connect cultural identity with the character development of students. This study aims to describe the educational values contained in Seloko Adat Melayu Jambi and to analyze their relevance to history learning at the senior high school level. This study employed a qualitative approach with a descriptive research design. Data were collected through field observations in Jambi City, in-depth interviews with traditional leaders, cultural figures, and history teachers, as well as documentation studies and analysis of literature related to seloko and history education. Data analysis was conducted through data reduction, data display, and conclusion drawing in accordance with the qualitative analysis model. The findings indicate that Seloko Adat Melayu Jambi contains five main educational values, namely religious, moral/ethical, social, cultural, and intellectual values. These values are aligned with the goals of character education and have strong relevance to the competencies of history learning at the senior high school level, particularly in strengthening understanding of local culture, fostering critical attitudes, and developing students’ identities. Seloko can be utilized as a contextual source of history learning because it links historical material with students’ real-life experiences, thereby enhancing meaning-making, cultural appreciation, and the overall quality of history learning based on local wisdom